Effects of Manipulation of Noradrenergic Activities on the Expression of Dopaminergic Phenotypes in Aged Rat Brains. (November 2021) - Zeng, Fei; Fan, Yan; Brown, Russell W.; Drew Gill, Wesley; Price, Jennifer B.; Jones, Thomas C.; Zhu, Meng-Yang
This study investigated the effects of the pharmacological manipulation of noradrenergic activities on dopaminergic phenotypes in aged rats. Results showed that the administration of L-threo-3, 4-dihydroxyphenylserine (L-DOPS) for 21 days significantly increased the expression of tyrosine hydroxylase (TH) and dopamine transporter (DAT) in the striatum and substantia nigra (SN) of 23-month-old rats. Furthermore, this treatment significantly increased norepinephrine/DA concentrations in the striatum and caused a deficit of sensorimotor gating as measured by prepulse inhibition (PPI). Next, old rats were injected with the α2-adrenoceptor antagonist 2-methoxy idazoxan or β2-adrenoceptor agonist salmeterol for 21 days. Both drugs produced similar changes of TH and DAT in the striatum and SN. Moreover, treatments with L-DOPS, 2-methoxy idazoxan, or salmeterol significantly increased the protein levels of phosphorylated Akt in rat striatum and SN. However, although a combination of 2-methoxy idazoxan and salmeterol resulted in a deficit of PPI in these rats, the administration of 2-methoxy idazoxan alone showed an opposite behavioral change. The in vitro experiments revealed that treatments with norepinephrine markedly increased mRNAs and proteins of ATF2 and CBP/p300 and reduced mRNA and proteins of HDAC2 and HDAC5 in MN9D cells. A ChIP assay showed that norepinephrine significantly increased CBP/p300 binding or reduced HDAC2 and HDAC5 binding on the TH promoter. The present results indicate that facilitating noradrenergic activity in the brain can improve the functions of dopaminergic neurons in aged animals. While this improvement may have biochemically therapeutic indication for the status involving the degeneration of dopaminergic neurons, it may not definitely include behavioral improvements, as indicated by using 2-methoxy idazoxan only.